The Effect of Market Power on Bank’s Net Interest Margin: The Moderating Role of Financial Access - I Made Pradityarjuna Mahatmyam Mahayana; Dony Abdul Chalid (Journal of International Conference Proceedings (JICP), 2021)
The research focuses on determining the effect of commercial bank’s market power on net interest margin and the moderating role of financial access. The study uses annual data of 33 commercial banks in Indonesia from 2012 to 2019 based on the category of State-Owned Commercial Banks and National Private Commercial Banks. The data is obtained from secondary data, using financial reports published by commercial banks. The data is analyzed using moderated regression analysis to estimate two models, basic model is used to estimate the effect of market power on net interest margin, while the interaction model is used to estimate the moderating effect of financial access. Market power was measured using the Lerner index of each bank. Financial access was measured by the number of branches and the availability of electronic banking channels such as mobile banking, internet banking, and digital branch. The results show that the increase in commercial bank’s market power significantly increases net interest margin. Other results also show that branch and mobile banking & internet banking significantly moderate the effect of market power on the net interest margin, while the digital branch is not significantly moderating the relationship between market power and net interest margin.